(untitled) (The Review of Diabetic Studies, 2024)
The rise of multidrug-resistant organisms (MDROs) presents a significant challenge in healthcare, particularly in tertiary care settings. This study examines the prevalence, antimicrobial sensitivity patterns, and associated risk factors of MDROs among 1,949 patients at King Abdullah Medical Complex in Saudi Arabia, with a focus on high-risk departments such as the ICU and CCU. Using a retrospective design, microbiology lab data from January 2023 to June 2024 was analyzed. Collected data included demographics, MDRO prevalence, and antimicrobial resistance rates. Statistical analyses, including Chi-square and ANOVA, evaluated the associations between MDRO prevalence and variables like age, gender, hospital department, and length of stay. Findings revealed that the ICU and CCU exhibited the highest MDRO prevalence, with older patients and those with extended hospital stays experiencing significantly higher MDRO rates. Klebsiella spp. and Acinetobacter spp. were the most common MDROs, displaying high resistance to carbapenems and moderate sensitivity to amikacin. The study underscores the need for targeted infection control measures and enhanced antimicrobial stewardship, particularly in critical care settings. These findings highlight the importance of continuous MDRO monitoring and resistance trend analysis to improve patient outcomes and curb resistance spread in healthcare facilities. Limitations include a single-hospital focus and retrospective design, suggesting future research should expand to multicenter and prospective studies.